Pengaruh Konsentrasi Nutrisi AB Mix dan Waktu Potong Ujung Tanaman Terhadap Pertumbuhan dan Produksi Tomat Buah Hidroponik Ducth Bucket System (DBS) - Fachri Septian, Achmad; Wahyuni, Endang Sri (JURNAL AGROPLANT, 2025)
This research aims to get the best concentration of AB Mix nutrients and the right time to cut the tip of the plant on the growth and production of fruit tomato plants (Solanum lycopersicum L.) hydroponic DBS. This research was conducted at the Greenhouse of the Islamic University of Jember, Jl. Kyai Mojo No.101, Kaliwates District, Jember Regency, East Java, 69 meters above sea level, from December 2023 to March 2024. The research was conducted using a 2x4 factorial completely randomized design (CRD) with 3 replications. The first factor is the concentration of AB Mix nutrients (N) with 2 levels, namely: N1 = 2000 ppm; and N2 = 2200 ppm. The second factor is plant tip cutting time (P) consisting of 4 levels, namely: P0 = No cutting; P1 = Cutting 14 HST; P2 = Cutting 21 HST; P3 = Cutting 28 HST. The observation parameters consisted of plant height, number of leaves, flower appearance, stem diameter, number of branches, number of fruits, fruit weight and sugar content. Observation data were analyzed with the F test to determine the effect of treatment. Results that differed significantly, continued with the LSD (Least Significant Difference) test at the 0.05 level using MS Excel software. The results showed that the concentration of AB Mix 2000 ppm gave the best effect on the parameters of plant height 35 HST and the number of fruits, while the concentration of AB Mix 2200 ppm gave the best effect on the parameters of plant height 21 HST, the beginning of flower emergence, stem diameter 35 HST and fruit weight. Cutting the tip of the plant 14 HST gives the best effect on the number of branches parameter. The interaction of AB Mix 2000 ppm nutrient concentration and without cutting the tip of the plant (NIP0) gave the best effect on plant height 35 HST; the interaction of AB Mix 2000 ppm nutrient concentration and cutting the tip of the plant 14 HST (N1P1) and the interaction of AB Mix 2000 ppm nutrient concentration and cutting the tip of the plant 21 HST (N1P2) gave the best effect on the number of fruits; and the interaction of AB Mix 2000 ppm nutrients and cutting the tip of the plant 28 HST gave the best effect on the number of leaves 30 HST.